Comparison of Skull Motions in Six Degrees of Freedom Between Two Head Supports During Frameless Radiosurgery by CyberKnife - Kang, Chen-Lin; Liu, Shyh-Chang; Wang, Jui-Chu; Liao, Kuan-Cho; Huang, Yu-Jie; Fang, Fu-Min; Liao, Tsung-I; Juan, Kuo-Jung; Huang, Chun-Chieh (Frontiers in Oncology, 2018)
Introduction: Maintaining immobilization to minimize skull motion is important during frameless radiosurgery. This study aimed to compare the intrafractional skull motions between two head supports. Methods: With 6D skull tracking system, 4,075 image records from 45 patients receiving radiosurgery by CyberKnife were obtained. Twenty-three patients used TIMO head supports (CIVCO) (Group A) and twenty-two patients used Silverman head supports (CIVCO) with MoldCare cushions (ALCARE) (Group B). The skull motions in X (superior-inferior), Y (right-left), Z (anterior-posterior) axes, 3D (three-dimensional) vector, Roll, Pitch and Yaw between the two groups were compared and the margins of planning target volume were estimated. Results: The translational motions in Group A were similar in three axes at initial but became different after 10 minutes, and those in Group B were less prominent in the Y axis. The rotational errors in Group A were most obvious in Yaw, but those in Group B were stationary in three axes. The motions in the X axis, 3D vector, Pitch and Yaw in Group B were significantly smaller than those in Group A; conversely, the motions in the Z axis in Group B were larger. To cover the 95% confidence intervals, margins of 0.77, 0.79 and 0.40 mm in the X, Y and Z axes, respectively, were needed in Group A, and 0.69, 0.50 and 0.51 mm were needed in Group B. Conclusions: Both head supports could provide good immobilization during the frameless radiosurgery. Silverman head support with MoldCare cushion was better than TIMO head support in the superior-inferior direction, 3D vector, Pitch and Yaw axes, but worse in the anterior-posterior direction.